Some methodical problems on allocating budget for marketing activities of enterprise - Thao, Vu Phuong (VNU Journal of Science: Legal Studies; Vol 20 No 1E, 2004)
Some business managers often assume that allocating budget for marketing activities of enterprises is the ‘’figure chewing work”, aiming at controlling, but not marketing. This point of view is completely erroneous. Marketing budgeting is a kind of decision which matters the marketing management of any enterprises because managers’ efforts in budgeting bring certain advantages to the marketing management and business operations of enterprises.